Religieus pluralisme als politiek probleem: Recente ontwikkelingen binnen pluralismeonderzoek - van 't Hul, Leonard (Religie & Samenleving, 2016)
In the last two decades, academic interest in the role of religious pluralism in developments within the religious landscapes of Western society expanded profoundly. This growing interest has crystallized into two distinct, albeit closely related lines of research. On the one hand, scholars tend to delve into the question of how the experience of religious pluralism reshapes individual religious identities and self-identification. On the other hand, scholars return to the question of how the state should deal with the growing variety of (non-institutional) faith-based identities. By taking three recent scholarly publications as a point of departure, this article provides a critical assessment of the dominant research outcomes in these two lines of research on religious pluralism. The central argument of the article is that current analyses on religious pluralism suffer from an ideological applauding of individual dynamics: scholars not only observe but also welcome the patterns of relativization and revitalization of individual identities. This is unfortunate from an analytical and normative-political point of view, for such applauding disregards processes of fundamentalization, and neglects the continued role that faith-based organizations play – for good or bad – in the religious landscape, and society writ large.